Dampak Judi Online terhadap Tingkat Perceraian di Langkat (Studi Kasus Pengadilan Agama Stabat Kelas IB Kabupaten Langkat) - Abdul Hakim; Muhammad Saleh; Suaib Lubis (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
Online gambling is a gambling game that is widespread among all levels of society. In this research, the impact that occurs due to husbands who are online gambling addicts leads to divorce. This case was determined by the Stabat Religious Court with case number 1519/Pdt.G/2023/PA.Stb. There are two points that are the main focus of this issue, with the aim of finding out the impact of online gambling on the divorce rate in Langkat district and then the decision of the Stabat Religious Court regarding divorce due to online gambling. This study uses a qualitative method. Data analysis using descriptive methods. This type of research is research using a normative legal approach method that examines literature studies, namely research on secondary data. Data collection techniques using interviews and documentation. The conclusion of this research is that the wife's petition for divorce was granted by the panel of judges at the Stabat Religious Court and charged all court costs to the Petitioner.